The Transition from Pediatric to Adult Health Care in Young Adults with Spina Bifida: Demographic and Physician-Related Correlates. Issue 3 (24th April 2022) - Stiles-Shields, Colleen; Kritikos, Tessa K.; Starnes, Meredith; Smith, Zoe R.; Holmbeck, Grayson N.
Abstract : This article has supplementary material on the web site: www.jdbp.org . ABSTRACT: Objective: This study examined the transition to adult health care for individuals with spina bifida (SB) and explored demographic and relational associations with transition status. Method: Young adults with SB (18–30; n = 326) were recruited to complete an anonymous, online survey. Frequencies of reported experiences, behaviors, and satisfaction with the transition to adult health care were examined. Nonparametric tests and exploratory hierarchical regressions were used to examine demographic and relational factors with physicians between those (1) who had and had not yet transitioned and (2) who did and did not return to pediatric care. Results: Most of the sample reported having transitioned to adult health care, with three-quarters reporting that their primary physician is an adult primary care doctor. Individuals who had transitioned were more likely to be younger ( p = 0.01) and to not have a shunt ( p = 0.003). Beyond the effect of age and shunt status, relational factors with pediatric providers were not associated with transition ( p > 0.1). After transition, over one-third reported returning to a pediatric provider. Those who did not return to pediatric care were more likely to have myelomeningocele, be a full-time student, and to not have a shunt ( p < 0.001). Beyond the effect of age and shunt status, lower ratings of communication with adult providers were associated with a return to pediatric care ( p = 0.04). Conclusion: The results highlight the need for additional research about barriers and facilitators to the transition to adult health care to target interventions that support this critical milestone in young adults with SB.